NV center creation in diamond by local CW laser irradiation of shallow implanted nitrogen - Alexius Enke; Nicole Raatz; Jan Meijer; Ralf Wunderlich (New Journal of Physics)
A novel creation procedure for the nitrogen-vacancy (NV) center in diamond is investigated. After shallow nitrogen implantation, a continuous-wave laser is used to induce NV formation, while simultaneously exciting fluorescence to enable live observation. Our investigations imply that a different mechanism than heat induced vacancy diffusion causes the formation of NV centers with this method and we suggest possible alternative pathways which could be responsible, based on the observed properties. Furthermore, we test the procedure for its capabilities for the controlled creation of single centers and show that the emergence of individual centers can be tracked, while achieving sub-micrometer spatial precision.